The Effect of Digital Marketing and E-WOM on Generation Z's Purchase Intention: The Mediating Role of Trust - Muhammad Fadhil Izzaini; Fani Firmansyah (Jurnal Investasi Islam, 2026)
Digital transformation drives Islamic banking to leverage digital marketing and electronic word of mouth (E-WOM) to increase purchase intention among Generation Z. However, previous studies have shown inconsistent results regarding the influence of these two variables on purchase intention, as well as a lack of research examining the role of trust as a mediating variable in the context of digital Islamic banking. This study aims to analyze the effect of digital marketing and E-WOM on the purchase intention of Generation Z users of Bank Syariah Indonesia (BSI) in Malang City, with trust as a mediating variable. The research uses a quantitative explanatory approach with 165 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that digital marketing does not have a significant effect on purchase intention (β = 0.127; p = 0.157) or trust (β = 0.187; p = 0.086), E-WOM has a positive and significant effect on purchase intention (β = 0.395; p < 0.001) and trust (β = 0.354; p = 0.001), trust does not have a significant effect on purchase intention (β = 0.131; p = 0.281), and is unable to mediate the influence of digital marketing or E-WOM on purchase intention. These findings indicate that E-WOM is the dominant factor in shaping purchase intention among Generation Z, while trust acts as a basic factor that does not directly drive usage intent. This study expands the literature on digital consumer behavior by showing that the role of trust is contextual among digital natives.